Developer Productivity: Navigating Common Pitfalls in Modern Engineering Organizations - Kuldeep Deshwal, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Developer productivity initiatives often backfire when organizations focus solely on output metrics without considering the human elements of software creation. This article examines common pitfalls that undermine developer effectiveness, including metric obsession, micromanagement, context-switching, ambiguous expectations, inadequate tooling, technical debt neglect, collaboration silos, deadline-driven development, feedback deprivation, and neglected well-being. By identifying these counterproductive patterns, engineering leaders can instead build sustainable productivity models centered on outcome-based measurement, developer autonomy, focused work environments, and continuous learning cultures. The goal shifts from maximizing short-term output to creating conditions where developers can consistently deliver high-quality solutions while maintaining motivation and sustainable work practices.
Keywords: Autonomy; Burnout; Collaboration; Feedback; Technical-Debt